2004
DOI: 10.1111/j.1365-2141.2004.05049.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of β‐catenin discriminates acute myeloid leukaemia from acute lymphoblastic leukaemia

Abstract: Summary The role of β‐catenin in epithelial neoplasms has been widely studied whereas current knowledge regarding β‐catenin gene and protein expression in bone marrow cells derived from normal haematopoiesis and clonal haematological disorders is lacking. β‐Catenin gene expression was quantitatively investigated in bone marrow cells derived from clonal haematological disorders [acute myeloid leukaemia (AML), acute lymphoblastic leukaemia (ALL), Philadelphia chromosome‐positive chronic myeloid leukaemia (Ph+ CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
5
27
0
1
Order By: Relevance
“…Since the overexpression of ␤-catenin results in tumor development in other tissues, we wondered why thymocytes do not respond in a similar manner. The lack of T-cell lymphomas in CAT-Tg mice was consistent with the absence of a documented role for ␤-catenin in human T-cell lymphomas (44,54). In this report, we demonstrate that the expression of oncogenic ␤-catenin in thymocytes at developmental stages that coincide with DNA recombination and a burst of proliferation induces DNA damage, growth arrest, and OIS in vivo.…”
supporting
confidence: 50%
“…Since the overexpression of ␤-catenin results in tumor development in other tissues, we wondered why thymocytes do not respond in a similar manner. The lack of T-cell lymphomas in CAT-Tg mice was consistent with the absence of a documented role for ␤-catenin in human T-cell lymphomas (44,54). In this report, we demonstrate that the expression of oncogenic ␤-catenin in thymocytes at developmental stages that coincide with DNA recombination and a burst of proliferation induces DNA damage, growth arrest, and OIS in vivo.…”
supporting
confidence: 50%
“…We confirm that b-catenin expression is rapidly lost upon myelomonocytic differentiation. 26,33 Interestingly, our preliminary results show that, depending on the way of maturation, erythroid for example, b-catenin could be reexpressed in CD34À cells (data not shown, and 33 ). We found that in M0-M2 AML patients (no M6 AML was tested), b-catenin expression was correlated with the median percentage of CD34 þ blasts, although this was not the case for M4-M5 AML.…”
Section: Discussionmentioning
confidence: 99%
“…In lymphoid neoplasms, the Wnt pathway has been found to play several important roles, such as proliferation, migration, and invasion [16,17]. In acute myeloid leukemia, the β-catenin gene expression has been found to be increased [18].…”
Section: Introductionmentioning
confidence: 99%